Разложи на множители 1−s2+2sd−d2 .

Выбери правильный ответ:
(1−s)⋅(1+s+2d)
(1−s+d)⋅(1+s−d)
(s−d)2
(1−s)⋅(1+d)
(s+d)2

gilewich gilewich    2   11.05.2020 15:42    2

Ответы
jonni0203 jonni0203  28.08.2020 21:15

1-s^2+2sd-d^2=1-(s^2-2sd+d^2)=1-(s-d)^2=\\\\=\Big(1-(s-d)\Big)\Big(1+(s-d)\Big)=\Big(1-s+d\Big)\Big(1+s-d\Big)

ответ: №2.

ПОКАЗАТЬ ОТВЕТЫ
ЮляКіска ЮляКіска  28.08.2020 21:15

Объяснение:

1-(s²-2sd+d²) =1-(s-d) ²=1²-(s-d) ²=

(1-(s-d)) *(1+(s-d)) =(1-s+d) *(1+s-d)

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра